Nanodiamonds as pH-switchable oxidation and reduction catalysts with enzyme-like activities for immunoassay and antioxidant applications. Issue 40 (10th October 2017) - Chen, T. M.; Tian, X. M.; Huang, L.; Xiao, J.; Yang, G. W.
Abstract : We have demonstrated that nanodiamonds (NDs), as oxidation and reduction catalysts, possess intrinsic enzyme mimetic properties of oxidase, peroxidase and catalase, and these behaviors can be switched by modulating the pH value. Abstract : Nanodiamonds (NDs) have recently become a focus of interest from the viewpoints of both science and technology. Their intriguing properties make them suitable as biologically active substrates, in biosensor applications as well as diagnostic and therapeutic biomedical imaging probes. Here, we demonstrate that NDs, as oxidation and reduction catalysts, possess intrinsic enzyme mimetic properties of oxidase, peroxidase and catalase, and these behaviors can be switched by modulating the pH value. NDs not only catalyze the reduction of oxygen (O2 ) and hydrogen peroxide (H2 O2 ) at acidic pH, but also catalyze the dismutation decomposition of H2 O2 to produce O2 at alkaline pH. It was proposed that the molecular mechanism of their peroxidase-like activity is electron-transfer acceleration, the source of which is likely derived from oxygen containing functional groups on their surface. Based on the color reaction, a nanodiamond-based enzyme linked immunosorbent assay (ELISA) was established for the detection of immunoglobulin G (IgG). Surprisingly, NDs display an excellent antioxidant activity due to the protective effect against H2 O2 -induced cellular oxidative damage. These findings make NDs a promising enzyme mimetic candidate and expand their applications in biocatalysis, bioassays and nano-biomedicine.